How to get rid of Gallant Soldier? - O. Kurdiukova; O. Ivaschenko (Карантин і захист рослин)
Goal. The goal of the research was to develop effective Galinsoga parviflora control techniques in crops of field and vegetable crops, taking into account its biological and environmental features.